The Urgency of China's Crypto Mining Ban in Relation to the Carbon Neutral Policy 2060 - Rossdiana, Renatha Ayu (Global Strategis, 2023)
Cryptocurrencies, specifically Bitcoin, which have been developing since 2008, are gaining increasing popularity due to their high value, considered the future of global finance. With its decentralized concept, crypto activities from mining to buying and selling can be carried out by individuals anywhere at any time. Nevertheless, despite its popularity, several countries, including China, have banned crypto activities, including the mining process. This paper further elaborates on why China has banned cryptocurrency mining. In conducting the analysis, the author uses the concept of sustainable development, the concept of a green economy and the concept of environmental security. As a result, this paper finds that the Chinese government banned crypto mining because of the government's commitment to the Carbon Neutral Policy 2060, where crypto mining is one of the economic sectors that contribute to carbon emissions on a large scale, driving an increase in e-waste and its operations that consume large amounts of energy. This condition contributes to a decrease in the quality of the environment so that its carbon footprint has the potential to become an obstacle for China in realizing its Carbon Neutral Policy. Keywords: carbon neutral policy, China, crypto mining, green economy, sustainable development environment   Mata uang kripto, secara spesifik Bitcoin yang marak berkembang sejak tahun 2008, semakin diminati banyak orang karena nilainya yang tinggi sehingga dianggap sebagai masa depan finansial global. Dengan sifatnya yang terdesentralisasi, aktivitas kripto mulai dari penambangannya hingga jual belinya dapat dilakukan oleh individu perseorangan dimanapun dan kapanpun. Namun, terlepas dari popularitasnya, beberapa negara termasuk Tiongkok melakukan pelarangan aktivitas kripto termasuk penambangannya. Tulisan ini mengelaborasi lebih lanjut pertanyaan mengapa Tiongkok melakukan pelarangan penambangan mata uang kripto. Penulis menggunakan konsep pembangunan berkelanjutan, konsep ekonomi hijau, dan konsep keamanan lingkungan. Hasilnya, tulisan ini menemukan bahwa pemerintah Tiongkok melakukan pelarangan penambangan kripto karena komitmen pemerintah terhadap Carbon Neutral Policy 2060, sebab penambangan kripto merupakan salah satu sektor ekonomi yang menyumbang emisi karbon dalam skala besar, mendorong kenaikan sampah elektronik, dan operasinya yang mengkonsumsi energi dalam jumlah besar. Kondisi ini berkontribusi pada penurunan kualitas lingkungan hidup sehingga jejak karbonnya berpotensi menjadi penghambat Tiongkok dalam mewujudkan Carbon Neutral Policy. Kata kunci: kebijakan karbon netral, Tiongkok, penambangan kripto, ekonomi hijau, pembangunan lingkungan berkelanjutan